FEATURES OF ARCHITECTURAL AND PLANNING ORGANIZATION OF RESIDENTIAL BUILDING OF THE RAISED DENSITY - Sydorenko, Artem; Zhovkva, Olga (Theory and practice of design, 2023)
This article analyzes the main principles underlying the design of high-density residential complexes. The main goal is to create comfortable and energy-efficient housing with high building density. The main design factors that will affect future projects with dense buildings are highlighted. Goal. The purpose of this article is to study and analyze the features of the architectural and planning organization of residential buildings with increased density in order to determine effective approaches and strategies for creating functional, comfortable and aesthetically attractive residential complexes. Methodology. The following methods are used: analysis of the composition and functionality of the building; a review of available research on high-density residential development; application of the formalization method; identification of factors influencing high-density residential development; systematization and generalization of domestic and international experience in this field. Result. During the research, the main characteristics in the design of high-density residential buildings were established, as well as the design principles of this type of housing were formulated. We carefully researched the international experience in designing affordable and dense housing. It was found that the most effective from an economic point of view is the use of dense buildings of average storeys in cities with different populations. We carefully evaluated the advantages and disadvantages of dense housing, and also took into account the current issues of determining the density of buildings according to modern trends. The main trends and characteristics corresponding to the needs and values of society are highlighted. We conducted an assessment of density achievement and presented examples of plans and facades for high-density residential development. Our research was based on scientific materials, which were used for a deep understanding of the studied issues. Scientific novelty. The analysis and substantiation of the methods of designing high-density residential buildings has been carried out. The main principles used in the design of this type of housing were improved and considered in detail. Practical significance. The obtained research results are a valuable contribution to the development of residential development projects with increased density, as they provide practical recommendations for achieving optimal results. Our deep understanding of external and internal factors influencing the design process allows us to effectively analyze and evaluate the impact of various factors on residential properties. The proposed architectural solutions and building characteristics play an important role in creating a comfortable living environment. Using these recommendations, we have the opportunity to develop innovative residential projects that ensure a high quality of life and meet the needs of residents.